Teaching Adults to Read Better and Faster : Results from an Experiment in Burkina Faso - Abadzi, Helen (World Bank, Washington, DC, 2014)
Two cognitively oriented methods were tested in Burkina Faso to help illiterates learn to read more efficiently. These were (a) speeded reading of increasingly larger word units and (b) phonological awareness training to help connect letters to speech. Learners were given reading tests and a computerized reaction time test. Although the literacy courses were shortened by the arrival of rains and government delays, the piloted methods helped adults read better than those in the standard "control" classes. Learners enrolled in the experimental classes performed better on the outcome tests than did learners enrolled in control classes. Ninety percent of the possible comparisons between treatment classes and control classes favored classes receiving treatments, and 72 percent of the measurements in favor of treatments were statistically significant. The evidence suggests that phonological awareness training is particularly effective in situations where the training period was short, and that rapid reading was more advantageous in longer training situations. Overall, the results are indicative of the potential that scientifically backed methods have in making adult literacy instruction more effective. However, due to the short duration of the classes (3-4 months) learners apparently did not receive sufficient practice to consolidate skills. Literacy skills may still be prone to being forgotten if readers do not learn to read automatically and if opportunities to read are few.